Relationship between Geriatric Syndromes, Urinary Incontinence and the Quality of Life of Elderly Patients in a Tertiary Care Hospital, Northeastern Thailand - สิงหาด สาวิตรี; กิตติวรเวช สุฬดี; กิตติวรเวช จำลอง; สุริยา อธิพงศ์; โภคทิพย์ สุเพียร (Journal of Health Science of Thailand, 2023)
The purpose of the study was to investigate the relationship between geriatric syndromes, urinary incontinence and the quality of life of elderly patients in a tertiary care hospital in Northeastern Thailand. The research was conducted by using descriptive research. Purposive sampling was used to recruit 346 patients aged 60 years and older who were admitted to the hospital. The instruments used in the study were (1) personal demographic questionnaires, (2) the International Consultation on incontinence questionnaire short form, (3) mini-mental state examination tool, (Thai version 2002), (4) Thai geriatric depression scale, (5) Thai Delirium Rating Scale, (6) fall risk assessment tool in the elderly, and (7) functional ability assessment form. The analysis used was descriptive statistics and inferential statistics such as chi-square and multiple logistic regression. The results showed that geriatric syndromes associated with urinary incontinence and the quality of life of elderly patients were dementia (OR, 2.84; 95%CI= 1.33-5.67), depression (R,1.36; 95%CI=1.00-1.73), and falls (OR,3.52; 95%CI=1.85-5.92). The results of this research could be used to develop a care program for geriatric syndromes and urinary incontinence in elderly patients in tertiary care hospitals and promote their health for a better quality of life.